2014
DOI: 10.5539/gjhs.v7n4p60
|View full text |Cite
|
Sign up to set email alerts
|

Research on Relationship Among Internet-Addiction, Personality Traits and Mental Health of Urban Left-Behind Children

Abstract: Aim:In this research, we attempted at exploring the relationships among urban left-behind children’s internet-addiction, personality traits and mental health.Methods:In the form of three relevant questionnaires (Adolescent Pathological Internet Use Scale, Eysenck Personality Questionnaire, Children’s Edition in Chinese and Mental Health Test), 796 urban left-behind children in China were investigated, concerning internet-addiction, personality traits and mental health.Results:(1) The internet-addiction rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 2 publications
3
46
0
1
Order By: Relevance
“…In the present study, anxiety, depression, negative self-esteem, somatization and hostility mean scores were found to be higher in the adolescents using Internet for more than 1 hour a day compared to the adolescents using Internet for an hour or less in a day. Studies support these results and demonstrate that there is a significant correlation between the mental health and Internet usage (Choi, Park, & Cha, 2017;Lai et al, 2015;Ying & Zhang, 2015). In the previous studies, excessive Internet use of adolescents was found to be associated with depression (Ho et al, 2014), hostility (Alpaslan, Avcı, Soylu & Guzel, 2014), anxiety (Ho et al, 2014), somatization (Cerutti, Presaghi, Spensieri, Valastro, & Guidetti, 2016), attention-deficit hyperactivity disorder (Yen, Ko, Yen, Wu, & Yang, 2007), and suicidal ideation (Alpaslan et al, 2014;I.…”
Section: Discussionmentioning
confidence: 59%
“…In the present study, anxiety, depression, negative self-esteem, somatization and hostility mean scores were found to be higher in the adolescents using Internet for more than 1 hour a day compared to the adolescents using Internet for an hour or less in a day. Studies support these results and demonstrate that there is a significant correlation between the mental health and Internet usage (Choi, Park, & Cha, 2017;Lai et al, 2015;Ying & Zhang, 2015). In the previous studies, excessive Internet use of adolescents was found to be associated with depression (Ho et al, 2014), hostility (Alpaslan, Avcı, Soylu & Guzel, 2014), anxiety (Ho et al, 2014), somatization (Cerutti, Presaghi, Spensieri, Valastro, & Guidetti, 2016), attention-deficit hyperactivity disorder (Yen, Ko, Yen, Wu, & Yang, 2007), and suicidal ideation (Alpaslan et al, 2014;I.…”
Section: Discussionmentioning
confidence: 59%
“…A previous study result [11] indicated that internet-addicted urban Total score 0.86 *** 0.87 *** 0.94 *** 0.92 *** 1 Note: *: p<0.05; **: p<0.01; ***: p<0.001 Table 2: Correlation coefficient between each factor of SSND and between each factor and SSND. left-behind children had characteristics such as anxiety, restlessness, introversion and difficulty in daily communication and that internet addiction had a certain prediction effect on personality trait, which conformed to symptoms expressed under deficiency of the four neurotransmitters.…”
Section: Status Quo Of Neurotransmitter Deficiency Of Internetaddictementioning
confidence: 92%
“…In aspect of gender, the deficiency extent on the four main neurotransmitters of left-behind male children was higher than that of left-behind female children (except that on DA), and there was a significant difference in γ-aminobutyric acid (GABA) deficiency extent between the both genders, which indicated that the neurotransmitter deficiency extent of the male children was severer than that of the female children. Generally, the internet addiction rate of male is higher than that of female [2,3,39] and such rule is still applicable in urban left-behind children [11]. High-addiction-level individuals seem to suffer severe neurotransmitter deficiency, but the internal relation is to be further explored.…”
Section: Status Quo Of Neurotransmitter Deficiency Of Internetaddictementioning
confidence: 99%
See 1 more Smart Citation
“…The test is a variation of the children's Manifest Anxiety Scale, a scale that has been widely used in the United States and other developed countries for more than a decade as a screening and clinical tool. Researchers have used this test extensively across China to measure the mental health of grade school students in urban contexts (Zhou ; Deng, Lei, and Cao ; Ge, Se, and Zhang ).…”
mentioning
confidence: 99%